1996
DOI: 10.1002/(sici)1522-7154(1996)2:4<167::aid-anxi2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs of anxiety disorders

Abstract: Anxiety disorders are estimated to affect 26.9 million individuals in the United States at some point during their lives. This study used the human capital approach to estimate the direct and indirect costs of these highly prevalent disorders. In 1990, costs associated with anxiety disorders were $46.6 billion, 31.5% of total expenditures for mental illness. Less than one‐quarter of costs associated with anxiety disorders were for direct medical treatment; over three‐quarters were attributable to lost or reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
148
2
9

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(159 citation statements)
references
References 12 publications
0
148
2
9
Order By: Relevance
“…These disorders are associated with a marked impairment in the quality of life of patients and their relatives [3,4] and incur huge economic costs [5]. A Dutch population study estimated the cost of anxiety disorders in a population of 1 million to be approximately $500 million per year [6].…”
Section: Introductionmentioning
confidence: 99%
“…These disorders are associated with a marked impairment in the quality of life of patients and their relatives [3,4] and incur huge economic costs [5]. A Dutch population study estimated the cost of anxiety disorders in a population of 1 million to be approximately $500 million per year [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, results of numerous surveys have indicated that anxiety disorders are extremely common in the American population. 1 In 1993, a follow-up of the 1988 Epidemiologic Catchment Area (ECA) study reported a 1-year prevalence of 12.3% for all anxiety disorders. 2 Further, the National Comorbidity Survey calculated a 1-year prevalence for anxiety disorders of 17.2% and suggested that 1 in 4 Americans (24.9%) would experience an anxiety disorder at some point in their lives.…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…Prompt detection and successful treatment can help reduce the overall costs of these debilitating disorders to individuals, families, social services, and the health care system. DuPont et al 1 estimated the total economic cost of anxiety disorders using the data set (derived from national surveys) and a cost estimation method developed by Rice 41 for use in public and health policy. Core costs were divided into direct costs (medical expenditures) and indirect costs (morbidity and mortality).…”
Section: Economic Aspects Of Anxiety Disordersmentioning
confidence: 99%
See 2 more Smart Citations